La Rivista di diritto coloniale. Une revue au service de la fondation du droit colonial italien - Toussaint Réthoré (Clio@Themis)
The Italian colonial law has been forged in a fragmented way, according to the requirements of the moment. Since the Italian Empire proclamation in 1936, it was essential for Italian colonialists to give Italian colonial law a true autonomy. The Rivista di diritto coloniale had been an important tool for this project. By the analysis of the Revue, published between 1936 and 1942, the articles it contents as well as the authors, we’ll try to determine how the revue served the organization of a scientific matter, the Italian colonial law.